Environmental attitudes in selected contemporary Malaysian novels in English: An eco-marxist perspective / Zainor Izat Zainal - Zainor Izat, Zainal (2016)

(untitled)
The field of environmental criticism has proliferated and inspired literary scholars from different parts of the world to participate in environmental discourse, discussing and deliberating on many environmental problems that vary in scale and scope. Criticism on Malaysian literature in English rarely addresses environmental concerns, and in this thesis, I attempt to redress this dearth by examining and critiquing four contemporary Malaysian novels in English: Keris Mas’ Jungle of Hope (2009), Yang-May Ooi’s The Flame Tree (1998), KS Maniam’s Between Lives (2003), and Chuah Guat Eng’s Days of Change (2010). The environmental complexities presented in these works differ, but the common thread in these works is the issue of land threatened by development plans. In these works, too, the land stands out as a trope for the environment in the Malaysian context. I discuss environmental attitudes expressed in these novels through issues such as alienation from nature, politics of the environment, development, and ethics. In order to explore attitudes towards these issues, this thesis draws on Eco-Marxism, a close reading of the texts using selected Marxist ecological insights and theory, informed by relevant postcolonial and environmental concepts/ideas; as well as historical and cultural changes — the ecological, economic, and political transformations that have occurred in Malaysia. Although Marxism is believed to lack an explicit perspective on ecology, we may still benefit from this theory, which provides the platform to dissect environmental issues in the Malaysian context. In this thesis, I argue that the writers exhibit a concerned attitude towards the environment, positioning their work as ‘lessons’ in nation-building, attesting to the tensions inherent in developing a country while maintaining and protecting the environment. This concerned attitude extends their apprehension in regards to humanity’s past and present relationship to the environment and foregrounds the urgency to sustain the environment for present and future generations vis-a-vis the iv rapid and dramatic transformations in Malaysian society — the consequences of capitalist modernisation, globalisation, and technological advancement. The writers’ answer to environmental degradation in Malaysia is relatively practical: a genuine commitment to the environment is crucial if we are to move towards sustainability. This commitment can be mediated through a sense of place, a strong and resilient civil society, a development paradigm that puts more emphasis on people and the environment, and an environmental ethics focused on duty, relationships, activism and sustainability. In a country like Malaysia, where nation-building is still a process rather than an end result, the need to examine and re-evaluate our environmental attitudes is crucial. In the realm of Malaysian literature in English, these novels serve as the most explicit form for such an endeavour.